Review: The effect of climate change on the distribution pattern of small pelagic fish around the world - ALFIRA YUNIAR; MUKTI ZAINUDDIN; RACHMAT HIDAYAT; SITI KHADIJAH SRIOKTOVIANA; SAFRUDDIN SAFRUDDIN; MUZZNEENA AHMAD MUSTAPHA; ST. AISJAH FARHUM (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yuniar A, Zainuddin M, Hidayat R, Srioktoviana SK, Safruddin, Mustapha MA, Farhum SA. 2024. Review: The effect of climate change on the distribution pattern of small pelagic fish around the world. Biodiversitas 25: 3325-3341. Small pelagic fish populations, which are critical to marine ecosystems and play a crucial part in food availability worldwide, are significantly impacted by climate change. Variations of small pelagic catch could be indicated by indices of climate variability such as AMO (Atlantic Multidecadal Oscillation), ENSO (El-Nino Southern Oscillation), IOD (Indian Ocean Dipole), and Monsoon. The purpose of this study was to provide important insight into the relationship of climate variability with the distribution of dominant species of small pelagic fish such as European sardines, mackerel, Decapterus sp., anchovy, and Sardinella sp. from 1974-2022. On average, the temperature optimum of small pelagic fish is generally 28.31±1.97°C, chlorophyll concentration of 0.68±0.37 mg.m-3, and salinity of 31.44±2.40 psu. In North Atlantic Waters, the dynamic migration and abundance of pelagic fish are influenced by the climate variability of AMO tharough the warm phase and cold phase. The impact of ENSO, IOD, and chlorophyll variability affect the distribution pattern and abundance of small pelagic species (mackerel, lemuru, anchovy, indian scad, and sardine) in tropical and subtropical waters. In the context of climate change impacts, the results show that small pelagic fish with a preference for warm temperatures tend to migrate to higher latitudes. Understanding the effect of climate change on the spatial and temporal dynamics of small pelagic fish could help improve the performance of future small pelagic fishing strategies and management around the world.